Analytic salinity-temperature relations for the upper-thermocline waters of the eastern North Atlantic subtropical gyre - Marrero-Diaz, Angeles; Rodriguez-Santana, Angel; Machin, Francisco; Pelegrí Llopart,José Luis (Scientia Marina, 2018)
We study the dependence of salinity on temperature in two by two degrees latitude-longitude boxes, for sur-face and upper-thermocline waters of the eastern North Atlantic subtropical gyre. The initial data set, from historical data-bases as well as from recent hydrographic cruises in the region, is carefully scrutinized to reject dubious measurements. Wesearch for polynomial relations of variable degree between salinity and temperature, the optimal fit is selected as the poly-nomial with the lowest degree that satisfies several statistical criteria. An independent hydrographic cruise is used to con-firm that the method performs substantially better than estimates from climatological data, and leads to relatively low devi-ations in geopotential anomaly and other derived quantities. An error propagation analysis using the Monte Carlo methodshows equally good results En este estudio caracterizamos la dependencia de lasalinidad con la temperatura en cajas de dos por dos grados de latitud y longitud para aguas superficiales y de la termoclinasuperior en el margen oriental del giro subtropical del Atlántico Norte. El conjunto inicial de datos, procedente de bases dedatos históricos, así como los procedentes de recientes campañas hidrográficas en la región, son cuidadosamente analizadospara eliminar las medidas de calidad dudosa. Se analizan varias relaciones polinómicas de grado variable para la salinidaden función de la temperatura, eligiendo como ajuste óptimo aquel polinomio de menor grado que satisface diversos criteriosestadísticos. Se utiliza una campaña hidrográfica independiente para confirmar que el método da resultados substancialmen-te mejores que estimaciones a partir de datos climatológicos, y que produce desviaciones relativamente bajas en la anoma-lía geopotencial y en otras magnitudes derivadas. Un análisis de la propagación del error usando el Método de Montecarlomuestra resultados igualmente buenos. 175 167 1,005 Q3 SCIE